Hollow core anti-resonant fibres with split cladding - Huang, Xiaosheng (2018)
A split cladding fibers (SCF) is proposed as an additional design to the anti-resonant type fiber. The introduced split cladding helps to reduce the fabrication distortion. We use numerical simulations to compare the Kagome fibers (KFs) and the proposed split cladding fibers (SCFs) over two normalized transmission bands. It reveals that SCFs are able to maintain the desired round shape of silica cladding walls, hence improving the confinement loss (CL) compared to the KF. Fabrication of the SCF is demonstrated by the stack-and-draw technique. The near filed mode patterns are measured to prove the feasibility of this fiber design.